2020
DOI: 10.1038/s41598-020-76619-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemotherapy and P2Et extract combination in ex-vivo derived tumor mammospheres from breast cancer patients

Abstract: The main cause of death by cancer is metastasis rather than local complications of primary tumors. Recent studies suggest that breast cancer stem cells (BCSCs), retains the ability to self-renew and differentiate to repopulate the entire tumor, also, they have been associated with resistance to chemotherapy and tumor recurrence, even after tumor resection. Chemotherapy has been implicated in the induction of resistant phenotypes with highly metastatic potential. Naturally occurring compounds, especially phytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Interestingly, there is an association between the immune cluster and the number of stem cell/epithelial–mesenchymal transition (EMT)-related gene signatures 15 . In a previous study by our group, we observed an accumulation of tumor cells of the ALDH + stem phenotype in response to NAT in all molecular subtypes except Her-2 16 . This finding suggests that the intrinsic differences of tumors may also play a role in the control of the microenvironment, as previously reported 17 19 .…”
Section: Introductionmentioning
confidence: 55%
“…Interestingly, there is an association between the immune cluster and the number of stem cell/epithelial–mesenchymal transition (EMT)-related gene signatures 15 . In a previous study by our group, we observed an accumulation of tumor cells of the ALDH + stem phenotype in response to NAT in all molecular subtypes except Her-2 16 . This finding suggests that the intrinsic differences of tumors may also play a role in the control of the microenvironment, as previously reported 17 19 .…”
Section: Introductionmentioning
confidence: 55%
“…Interestingly, there is an association between the immune cluster and the number of stem cell/epithelial-mesenchymal transition (EMT)related gene signatures 15 . In a previous study by our group, we observed an accumulation of tumor cells of the ALDH + stem phenotype in response to NAT in all molecular subtypes except Her-2 16 . This finding suggests that the intrinsic differences of tumors may also play a role in the control of the microenvironment, as previously reported [17][18][19] .…”
Section: Introductionmentioning
confidence: 55%
“…The central research area of our group is the study and development of phytomedicines from Colombian plants, among them Petiveria alliacea (P. alliacea), Caesalpinia spinosa (C. spinosa), Tillandsia usneoides (T. usneoides), and Piper nigrum (P. nigrum) (Lasso et al, 2018;Urueña et al, 2020;Lasso et al, 2022;Urueña et al, 2022). Each one of the extracts of these plants has been characterized from a chemical point of view, and the main compounds have been isolated and studied.…”
Section: Immunomodulationmentioning
confidence: 99%